2015
DOI: 10.1371/journal.pone.0121966
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Cartilage May Be a Chondroinductive Material for Osteochondral Tissue Engineering

Abstract: Extracellular matrix (ECM)-based materials are attractive for regenerative medicine in their ability to potentially aid in stem cell recruitment, infiltration, and differentiation without added biological factors. In musculoskeletal tissue engineering, demineralized bone matrix is widely used, but recently cartilage matrix has been attracting attention as a potentially chondroinductive material. The aim of this study was thus to establish a chemical decellularization method for use with articular cartilage to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
118
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 30 publications
8
118
1
Order By: Relevance
“…1A-C). In prior work, it was established that no significant reduction in biochemical content was observed between native cartilage and cartilage that was cryoground, 17 so the prior mentioned reductions are in reference to DVC powder.…”
Section: Characterization Of Meha Dvc and DCC Microparticlesmentioning
confidence: 99%
See 3 more Smart Citations
“…1A-C). In prior work, it was established that no significant reduction in biochemical content was observed between native cartilage and cartilage that was cryoground, 17 so the prior mentioned reductions are in reference to DVC powder.…”
Section: Characterization Of Meha Dvc and DCC Microparticlesmentioning
confidence: 99%
“…17 In the pellet culture study, we observed that rat bone marrow stem cells (rBMSCs) exposed to DCC outperformed those cells exposed to DVC or transforming growth factorb 3 (TGF-b 3 ) in chondroinductivity. 17 However, gene expression was only observed over a period of 7 days and was only monitored for cells in pellet culture and not within a 3D scaffold.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nanotubes Can affect the cells and the cell morphology alter through the nanostructured surface. thus CNT-based surfaces provide a very good scaffold that can be used to stimulate the formation of cartilage tissue (Sutherland et al 2015 andTrzeciak et al 2016). We tried to keep natural structure of decellularized cartilage intact and put it close to nanotubes in such an environment.…”
Section: Resultsmentioning
confidence: 99%